GROWTH MINDSET DEVELOPMENT: A CASE STUDY OF ADMINISTRATORS IN ROYAL AWARDED ELEMENTARY SCHOOLS IN PHATTHALUNG - Sungtong, Ekkarin; Thupaang, Anupap; Palamicho, Pakinee; Kongplub, Wantira; Choosang, Orachorn (Journal of Educational Review Faculty of Education in MCU, 2024)
This qualitative case study research aims to investigate the development of the growth mindset of administrators in Royal awarded elementary schools in Phatthalung. Key participants recruited by purposive sampling were ten people, including two school administrators, four teachers, two heads of the academic administration, and two heads of the general administration. A semi-structured interview protocol served as the primary tool for gathering research data. Content analysis was employed to do the data analysis. The credibility of this study was enhanced through the strategic use of rapport and peer debriefing. The result reveals that the development of the administrators’ growth mindset includes: 1) believing in intellectual capability: the administrators possess knowledge, morality, dignity, vision, and ability to apply theories to their school administration; 2) being open to new challenges: the administrators are enthusiastic and confident to consider challenges as opportunities by building networks and opening to modern technology; 3) searching for role models and inspiration: the administrators seek for the role models to follow for their achievements and rewards; 4) accepting opinions and criticism from personnel: the administrators are open to everyone’s opinions and learn from feedback; 5) persistence to obstacles: the administrators consider problems as opportunities and have confidence in their abilities to handle problems; and 6) resilience and flexibility: the administrators are open-minded and adapt to different situations.